2012
DOI: 10.1146/annurev-publhealth-031811-124540
|View full text |Cite
|
Sign up to set email alerts
|

Advertising of Prescription-Only Medicines to the Public: Does Evidence of Benefit Counterbalance Harm?

Abstract: Since the global withdrawal of rofecoxib (Vioxx) in 2004, concerns about public health effects of direct-to-consumer advertising (DTCA) have grown. A systematic review of the research evidence on behavioral, health, and cost effects, published in 2005, found four studies meeting inclusion criteria, which showed that DTCA increases prescribing volume and patient demand, and shifts prescribing. From 2005 to 2010, nine studies met similar criteria. These largely confirm previous results. Additional effects includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 81 publications
0
59
0
Order By: Relevance
“…5 Thus far, the limited evidence-of varying methodological quality-on the effects of DTCA is inconclusive. 6 Numerous studies have investigated the impact of DTCA on prescription drug use. Previous time series analyses have shown that DTCA was associated with increased volume of prescriptions for tegaserod (the only available medication for irritable bowel syndrome), antihistamines (first-line therapy for allergic rhinitis), statins (hyperlipidemia), histamine H 2 -receptor antagonists (acid reflux), triptans (migraine), and terbinafine (onychomycosis).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Thus far, the limited evidence-of varying methodological quality-on the effects of DTCA is inconclusive. 6 Numerous studies have investigated the impact of DTCA on prescription drug use. Previous time series analyses have shown that DTCA was associated with increased volume of prescriptions for tegaserod (the only available medication for irritable bowel syndrome), antihistamines (first-line therapy for allergic rhinitis), statins (hyperlipidemia), histamine H 2 -receptor antagonists (acid reflux), triptans (migraine), and terbinafine (onychomycosis).…”
Section: Introductionmentioning
confidence: 99%
“…Previous time series analyses have shown that DTCA was associated with increased volume of prescriptions for tegaserod (the only available medication for irritable bowel syndrome), antihistamines (first-line therapy for allergic rhinitis), statins (hyperlipidemia), histamine H 2 -receptor antagonists (acid reflux), triptans (migraine), and terbinafine (onychomycosis). [6][7][8][9][10] In contrast, DTCA for drugs such as etanercept (for symptom refractory rheumatoid arthritis), mometasone (second-line therapy for allergic rhinitis), and clopidogrel (anti-platelet agent for acute coronary syndrome or following percutaneous intervention) have not been shown to alter prescribing rates. 7,11 Overall, it appears from the existing body of evidence that when DTCA has been shown to increase prescribing volume, it typically involves greater use of medications for common and underdiagnosed diseases.…”
Section: Introductionmentioning
confidence: 99%
“…DTCA has become a prominent part of both the mass and online media landscape for nearly 20 years, and has been shown to influence patient demand and prescribing decisions, to be associated with shifts to less appropriate prescribing and less cost-effective treatments, and to maintain sales despite a price increase. 1 Online DTCA is an integral part of these campaigns. The AMA's call for a ban on DTCA in 2015 follows a 2007 US Institute of Medicine call for a moratorium on DTCA in the first two years post approval as a safety measure, as new evidence of serious harm often emerges within this period.…”
Section: Resultsmentioning
confidence: 99%
“…This far exceeds the 15 min a year the average American spends with a primary care physician [1,2]. Manufacturers spent $4.3 billion in 2010 on drug advertisements aimed directly at the consumer, and television is the largest source of pharmaceutical DTCA expenditure and exposure [3,4].…”
Section: Introductionmentioning
confidence: 98%
“…Direct-to-consumer advertising for pharmaceutical products (DTCA) has rapidly become the second most frequently advertised consumer product on TV in the United States (US), with American viewers exposed to approximately 16 h of DTCA per year [1][2][3]. The sheer volume of pharmaceutical DTCA exposure has prompted researchers to test its potential effects, both intended and unintended.…”
Section: Introductionmentioning
confidence: 99%